2018
DOI: 10.1101/266205
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Feature Specific Prediction Errors and Surprise across Macaque Fronto-Striatal Circuits during Attention and Learning

Abstract: HighlightsNeural reward prediction errors carry information for updating feature-based attention in all areas of the fronto-striatal network.Feature specific neural prediction errors emerge earliest in anterior cingulate cortex and later in lateral prefrontal cortex.Ventral striatum neurons encode feature specific surprise strongest for the goal-relevant feature.Neurons encoding feature-specific prediction errors contribute to attentional selection after learning.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 98 publications
1
14
0
Order By: Relevance
“…During reversal performance we recorded the activity of 329 single neurons in LPFC areas 46/9 and anterior area 8 (monkey H/K: 172/157) and 397 single neurons in dorsal ACC area 24 (monkey H/K: 213/184) (Figure 1D, Figure 1-figure supplement 1). The average action potential waveform shape of recorded neurons distinguished neurons with broad and narrow spikes similar to previous studies in LPFC and ACC (Gregoriou et al, 2012;Ardid et al, 2015;Westendorff et al, 2016;Dasilva et al, 2019;Oemisch et al, 2019) (Figure 1E). Prior biophysical modeling has shown that the extracellular action potential waveform shape, including its duration, is directly related to transmembrane currents and the intracellularly measurable action potential shape and duration (Gold et al, 2006;Bean, 2007;Gold et al, 2007;Buzsaki et al, 2012).…”
Section: Characterizing Narrow Spiking Neurons As Inhibitory Interneuronssupporting
confidence: 85%
See 3 more Smart Citations
“…During reversal performance we recorded the activity of 329 single neurons in LPFC areas 46/9 and anterior area 8 (monkey H/K: 172/157) and 397 single neurons in dorsal ACC area 24 (monkey H/K: 213/184) (Figure 1D, Figure 1-figure supplement 1). The average action potential waveform shape of recorded neurons distinguished neurons with broad and narrow spikes similar to previous studies in LPFC and ACC (Gregoriou et al, 2012;Ardid et al, 2015;Westendorff et al, 2016;Dasilva et al, 2019;Oemisch et al, 2019) (Figure 1E). Prior biophysical modeling has shown that the extracellular action potential waveform shape, including its duration, is directly related to transmembrane currents and the intracellularly measurable action potential shape and duration (Gold et al, 2006;Bean, 2007;Gold et al, 2007;Buzsaki et al, 2012).…”
Section: Characterizing Narrow Spiking Neurons As Inhibitory Interneuronssupporting
confidence: 85%
“…We used a color-based reversal paradigm that required subjects to learn which of two colors were rewarded as described previously (Oemisch et al, 2019). The rewarded color reversed every ~30-40 trials.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the number of converging projections to the STR 32 makes it prone to detect environmental changes from multiple brain sources beyond the mPFC. Hence, the STR may provide a different action selection and, consequently, a different strategy to optimize reward rate 29, 33 .…”
Section: Discussionmentioning
confidence: 99%